A Discourse on the Legal Implications of Digital Standard Contracts in the Context of Personal Data Protection - Debora, Debora; Simamora, Janpatar; Manullang, Herlina; Tambunan, Mika Thensia (Jurnal Pembaharuan Hukum, 2025)
This paper examines the legal aspects of the use of standard digital contracts with respect to the protection of users' personal data and the control of their use. This research takes a normative approach. Standard terms are not prohibited, but the inclusion of exculpatory clauses is prohibited under Article 18 of the Consumer Protection Act. Digital practices recognize standard digital contracts related to personal data. Article 20 of the Personal Data Protection Law requires a valid legal basis for the processing of personal data. The legal basis is set out in a digital contract between the personal data controller and the personal data subject. The standard contract must contain all the things required by the Personal Data Protection Act. The personal data subject has the right to obtain information about the clarity of identity, the basis of legal interests, the purpose of requesting and using the personal data and the responsibility of the party requesting the personal data. Supervision of the use of digital standard agreements is carried out by the BPSK and the OJK after the digital standard agreements have been implemented by business entities. This form of supervision is less effective in maintaining the balance of the parties.